2021
DOI: 10.1007/s11423-021-09979-2
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative note-taking affects cognitive load: the interplay of completeness and interaction

Abstract: Studies showing improved learning performances for students who take notes collaboratively have speculated that sharing this task among group members may reduce the extraneous cognitive burden placed on each member. Therefore, a study (n = 171) was conducted in the context of a flipped scientific writing course to examine the effects of collaborative note-taking on student’s levels of cognitive load. Students in the course were divided into two groups, with members of the treatment group being directed to take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Besides, during the PBL activity, students can work collaboratively to edit the computer‐mediated structured whiteboard. Examining the effect of collaborative note‐taking on students' level of cognitive load, researchers showed that students' collaboration level was positively related to their germane load to understand the course content but was not associated with their extraneous load of learning confusion (Costley & Fanguy, 2021). Thus, as a measure to increase germane load and reduce extraneous load, this study would adopt the computer‐mediated structured whiteboard for both the control and experimental groups to assist their collaborative problem‐solving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, during the PBL activity, students can work collaboratively to edit the computer‐mediated structured whiteboard. Examining the effect of collaborative note‐taking on students' level of cognitive load, researchers showed that students' collaboration level was positively related to their germane load to understand the course content but was not associated with their extraneous load of learning confusion (Costley & Fanguy, 2021). Thus, as a measure to increase germane load and reduce extraneous load, this study would adopt the computer‐mediated structured whiteboard for both the control and experimental groups to assist their collaborative problem‐solving.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Collaborative activities where group members attempt to collectively record and build knowledge will help to deepen their understanding of course concepts and improve retention. This occurs because students can share the burden of recording information, which can free cognitive resources to make deeper connections with the content (Costley & Fanguy, 2021). Collaborative note-taking from this perspective is situational.…”
Section: Pedagogical Recommendationsmentioning
confidence: 99%
“…Working memory capacity and time constraints are important factors in cognitive load. Costley & Fanguy (2021) discuss the limited capacity of working memory and the three types of cognitive load imposed on it: extraneous, germane, and intrinsic. These references emphasize that collaboration work can increase the cognitive load by imposing extraneous and germane cognitive load, especially when there are multiple novel and interacting information elements to be processed simultaneously (Klepsch & Seufert., 2020;Costley & Fanguy, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Costley & Fanguy (2021) discuss the limited capacity of working memory and the three types of cognitive load imposed on it: extraneous, germane, and intrinsic. These references emphasize that collaboration work can increase the cognitive load by imposing extraneous and germane cognitive load, especially when there are multiple novel and interacting information elements to be processed simultaneously (Klepsch & Seufert., 2020;Costley & Fanguy, 2021). Digital platforms can help reduce the extraneous load by providing a more organized and structured learning environment (Skulmowski & Xu., 2021).…”
Section: Introductionmentioning
confidence: 99%